2010
DOI: 10.4317/medoral.15.e658
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure alterations of rotary files after multiple simulated operative procedures

Abstract: Aim: To assess morphological alterations of ProTaper rotary NiTi files before and after continuous use by scanning electron microscopy (SEM). Study Design: 30 root canals were chosen with an angle between 15 and 30º. Before starting to prepare the canals the files were observed microscopically using a scanning electronic microscope. The ProTaper sequence recommended by the manufacturer was used, with NaOCl as irrigant. The instruments were sterilised after every three canals were shaped. The instruments were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 17 publications
1
13
0
1
Order By: Relevance
“…This method has been used in other studies (Tripi et al 2001, Troian et al 2006, Luzi et al 2010) and has been accepted for the accurate evaluation of deformation of instruments (Troian et al 2006). This method has been used in other studies (Tripi et al 2001, Troian et al 2006, Luzi et al 2010) and has been accepted for the accurate evaluation of deformation of instruments (Troian et al 2006).…”
Section: Discussionmentioning
confidence: 98%
“…This method has been used in other studies (Tripi et al 2001, Troian et al 2006, Luzi et al 2010) and has been accepted for the accurate evaluation of deformation of instruments (Troian et al 2006). This method has been used in other studies (Tripi et al 2001, Troian et al 2006, Luzi et al 2010) and has been accepted for the accurate evaluation of deformation of instruments (Troian et al 2006).…”
Section: Discussionmentioning
confidence: 98%
“…In addition, the presence of surface irregularities on NiTi files (24) may compromise their cutting efficiency (25) and probably make them more susceptible to corrosion and fracture (26). The s-shaped cross-sectional design of Mtwo files results in very aggressive cutting edges and a positive rake angle, which is known to require less energy to cut dentin than blades with a neutral or negative rake angle (27), leading to less crack and surface irregularities on the file, which increases corrosion resistance.…”
Section: Discussionmentioning
confidence: 99%
“…This is very troublesome, especially in clinical use where the mean lifetime (mean NCF) has shown no clinical relevance. In addition, using scanning electron microscopy 24,25) , unused NiTi instruments were found to contain at least one defect. After clinical single use, Arens et al 26) found that 14% of NiTi instruments showed various defects and 0.9% fractured.…”
Section: Discussionmentioning
confidence: 99%